2014
DOI: 10.1530/eje-13-0848
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral adrenal incidentalomas differ from unilateral adrenal incidentalomas in subclinical cortisol hypersecretion but not in potential clinical implications

Abstract: Objective: To investigate the possibility of a different prevalence of subclinical Cushing's syndrome (SCS) and potentially related morbidities between patients with unilateral adrenal incidentalomas (UAI) and bilateral adrenal incidentalomas (BAI), as existing data are few and controversial. Design: Prospective observational study. Methods: Clinical examination, biochemical tests, and hormonal evaluation were performed in 298 consecutive patients with adrenal incidentalomas, unilateral in 224 patients (75.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
39
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 34 publications
(59 reference statements)
11
39
1
Order By: Relevance
“…Accordingly, other recent studies found an increased prevalence of glucose tolerance abnormalities among patients with sCS compared to patients with nonfunctioning adrenal adenomas (15). The prevalence of glucose metabolism abnormalities in patients with monolateral vs bilateral adrenal lesions is the same, even if sCS was more frequent among patients with bilateral disease (18). Insulin sensitivity parameters were reduced in both non-functioning adrenal adenoma or in sCS, compared to healthy controls.…”
Section: Gcs and Glucose Metabolismmentioning
confidence: 81%
“…Accordingly, other recent studies found an increased prevalence of glucose tolerance abnormalities among patients with sCS compared to patients with nonfunctioning adrenal adenomas (15). The prevalence of glucose metabolism abnormalities in patients with monolateral vs bilateral adrenal lesions is the same, even if sCS was more frequent among patients with bilateral disease (18). Insulin sensitivity parameters were reduced in both non-functioning adrenal adenoma or in sCS, compared to healthy controls.…”
Section: Gcs and Glucose Metabolismmentioning
confidence: 81%
“…In total, 12 studies were included: 7 cross-sectional studies (38,42,43,45,141,142,143) and 5 cohort studies (40,46,144,145,146). In eight studies, a comparison was made between patients with elevated (group 1) or normal (group 2) cortisol levels after a 1 mg dexamethasone test.…”
Section: Assessment Of Autonomous Cortisol Secretion In Relation To Cmentioning
confidence: 99%
“…4,5 Surgery is generally recommended for larger or growing lesions, as well as those with hormonal hypersecretion. Although the workup of bilateral and unilateral incidentalomas is similar, the results of small studies [6][7][8] suggested differences in the 2 groups. We sought to determine the characteristics and natural history of patients having bilateral adrenal incidentalomas to provide greater insight into their workup and management.…”
mentioning
confidence: 93%